2010
DOI: 10.1007/s10787-010-0051-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of constitutive nitric oxide synthase S-nitrosylation in Helicobacter pylori-induced gastric mucosal cell apoptosis: effect of ghrelin

Abstract: Infection with H. pylori is a primary factor in the etiology of gastric disease, and the excessive NO generation and a massive rise in apoptosis are well recognized features that characterize the mucosal inflammatory responses to the bacterium and its lipopolysaccharide (LPS). Here, we report that H. pylori LPS-induced enhancement in gastric mucosal cell apoptosis and NO generation was associated with the suppression in constitutive nitric oxide synthase (cNOS) activity and a marked up-regulation in the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 32 publications
5
19
0
Order By: Relevance
“…Our results demonstrate that the LPS-induced abrogation of cNOS control over NF-κB activation results in the induction of iNOS expression and leads to COX-2 activation through S-nitrosylation. Moreover, our results show that peptide hormone, ghrelin, recognized for its modulatory control over NOS and COX enzyme systems [16,[22][23][24][25], suppresses these untoward consequences of the LPS through up-regulation in cNOS activation that interferes with NF-κB nuclear translocation, thus causing the repression of iNOS gene induction and the inhibition of COX-2 activation through iNOS-dependent S-nitrosylation.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…Our results demonstrate that the LPS-induced abrogation of cNOS control over NF-κB activation results in the induction of iNOS expression and leads to COX-2 activation through S-nitrosylation. Moreover, our results show that peptide hormone, ghrelin, recognized for its modulatory control over NOS and COX enzyme systems [16,[22][23][24][25], suppresses these untoward consequences of the LPS through up-regulation in cNOS activation that interferes with NF-κB nuclear translocation, thus causing the repression of iNOS gene induction and the inhibition of COX-2 activation through iNOS-dependent S-nitrosylation.…”
Section: Introductionmentioning
confidence: 71%
“…The cross-talk between the products of NOS and COX pathways is supported by the studies indicating that stimulation of NO production through iNOS induction leads to COX enzymes activation and the increase in PGE 2 generation, whereas NOS gene deletion or inhibition of NOS enzymes with pharmacological agents results in a decrease in PGE 2 formation [9][10][11][12]. The role of cNOS in the iNOS-dependent COX-2 activation has also been suggested [10,13], and we have reported that the disturbances in NO and PGE 2 generation elicited by H. pylori LPS are reflected in the massive up-regulation of iNOS and COX-2 activity, and the suppression in Src/Aktdependent cNOS activation [14][15][16].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations